Synthesis of Truncated Carbocyclic Nucleosides Using 5′‐Deoxy‐5′‐Heteroarylsulfonylnucleosides. Issue 3 (23rd March 2022) - Oka, Natsuhisa; Kanda, Mayuka; Furuzawa, Minami; Arai, Wakaba; Ando, Kaori
Abstract: This article describes the detailed protocol for the synthesis of "truncated" carbocyclic nucleosides with a cyclopentene core and without a 4′‐hydroxymethyl group. The synthesis was performed using 5′‐deoxy‐5′‐heteroarylsulfonylnucleosides, which were prepared by the 5′‐ O ‐mesylation of the appropriately protected nucleosides, followed by a nucleophilic substitution with heteroarylthiols and the oxidation of the resulting 5′‐ S ‐heteroaryl‐5′‐thionucleosides. The treatment of the 5′‐deoxy‐5′‐heteroarylsulfonylnucleosides with 1, 8‐diazabicyclo[5.4.0]undec‐7‐ene affords the truncated carbocyclic nucleosides, presumably via a domino reaction involving the α‐deprotonation of the heteroarylsulfone, elimination of the nucleobase, formation of an α, β‐unsaturated sulfone, Michael addition of the nucleobase to the α, β‐unsaturated sulfone, and an intramolecular Julia‐Kocienski reaction. This protocol would be useful for the short‐step synthesis of biologically active carbocyclic nucleosides. © 2022 Wiley Periodicals LLC. Basic Protocol 1 : Preparation of 5′‐deoxy‐5′‐heteroarylsulfonylnucleosides Basic Protocol 2 : Synthesis of truncated carbocyclic nucleosides